Advances in spectral techniques for fruit quality evaluation: case of ULF-NMR and NIRS - Isingizwe Nturambirwe, Jean Frederic (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.